Biophilic Design as A Source of Inspiration in The Development of Creativity Process: An Example of Interior Architecture Design Studio - Dilek Yasar (Architecture Image Studies Scientific Journal)
Based on taking advantage of the healing power and aesthetic wealth of nature, biophilic design theory has had an important place in the architectural literature for the last few decades. Previous studies suggested that biophilic design was not only a part of theoretical debate among scholars but also had practical implications. In fact, a wealth of studies suggested that buildings, and especially the interiors, designed upon biophilic design approach, sustained positive impact on the health and well-being of users and significantly increased the performance and creativity levels. In that regard, biophilic design can make a significant contribution to the development of creativity in design education setting. Furthermore, biophilic design can also provide guidance on how creativity should be incorporated into learning and teaching experiences. Therefore, inclusion of biophilic design in design education curriculum would be beneficial for both students and instructors. Although for centuries nature has been used as an aesthetic model for design, biophilic design has an important potential as a design education paradigm thanks to the fact that it has certain principles and a systematic. The present article aimed to introduce the biophilic design theory, underscore its significance, and suggest how the theory could make a contribution to learning and teaching processes by fostering creativity in interior design education setting. Accordingly, how biophilic design strategies nurtured and developed creative thinking skills was demonstrated on the basis of design outputs of the 6th semester interior design studio. The results suggested that the students included rich patterns of nature in their designs with an artistic sensitivity, used colors, textures, and motifs similar to those in nature, and showed a tendency to include visual folds and/or elevation differences in interiors similar to those found in nature. Furthermore, they exhibited better protective behavior towards the natural environment in their designs.